Factors Affecting Health-Related Quality of Life in Tuberculosis Patients: A Systematic Review - Yousaf, Ruhamah; Elengoe, Asita; Riaz , Muhammad; Shah, Abid Hussain (Pakistan Armed Forces Medical Journal, 2025)
Objective: To systematically review and synthesize published evidence on the physical, psychosocial, and socioeconomic factors influencing health-related quality of life (HRQoL) among patients with tuberculosis (TB). Data Sources: This study used four primary databases (PubMed, Scopus, Medline, and Web of Science). MeSH terms and keywords (“TB”, “QoL”, “HRQoL”, “PROMs”, “patient reported outcomes”) with Boolean operators to identify global peer-reviewed studies on TB about HRQoL and sociodemographic variables. Study Selection: English-language, open-access articles (2012-2024) on adult TB patients’ HRQoL using quantitative or qualitative methods were included. Studies on pediatric, extrapulmonary TB populations or specific comorbidities, and non-original articles were excluded. Screening was performed by two independent reviewers, with arbitration as needed. Data Extraction: Using a standardized PRISMA-guided approach data was summarized for study characteristics and HRQoL domains (physical, psychological, and socioeconomic). Meta-analysis was not conducted due to heterogeneity in study designs, measurement tools, and outcomes. Data Synthesis: Twenty-nine studies revealed that TB significantly impairs HRQoL, persistent physical symptoms, early psychological distress (e.g., depression, anxiety), and socioeconomic hardship were common. Stigma and low social support further reduced the adherence and well-being. Peer and nutritional support showed positive effects but underutilized. Conclusion: This review underscores the broad impact of TB on HRQoL, with persistent physical symptoms, psychological distress, stigma-related isolation and socioeconomic hardship. Findings emphasize the need for community-based support and integrated policies to enhance recovery and reintegration beyond medical treatment.